'Optimal honesty' in the context of fiscal crimes - Lory Barile; John G. Cullis; Philip R. Jones (Economies, 2024)
This paper begins by contrasting the caricatures 'homo and femina economicus' with 'homo and femina realitus'. Against this backdrop, the paper considers three 'apparently falsified' empirical predictions of the standard expected utility model of individual decision-making concerning participation in fiscal crimes: that tax evasion and benefit fraud can be treated identically; fiscal crimes should be endemic; and that all individuals, depending on parameter values, should be either honest or dishonest. A utility function relating to decisions with a moral dimension is used to offer insight into the rationalization of the predictions and involves defining an individual's 'optimal honesty' in the context of fiscal crimes. The policy implications of the approach are briefly explored.
Keywords: D00; H26; H5; K42; 330; benefit fraud; moral costs; optimal honesty; tax evasion